The impact of context-aware fisheye models on understanding business processes: An empirical study of data flow diagrams - Turetken, Ozgur; Schuff, David (Information & management, 2007)
We investigated whether a “context-aware” fisheye view can more successfully communicate the information contained in a set of process models (data flow diagrams) than a traditional “context-free” presentation. We conducted two controlled experiments: the first included a simple set of DFDs and tasks that required a basic understanding of the system, while the second involved more detailed views of the same processes, and also a more complex task. Subjects who used the fisheye process models outperformed those using the traditional presentations. This difference was reflected in task performance for all subjects, and in task completion time for inexperienced subjects.